2018
DOI: 10.1093/jhps/hny022
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopy and arthrotomy to address intra-articular pathology during PAO for hip dysplasia demonstrates similar short-term outcomes

Abstract: Periacetabular osteotomy (PAO) remains the gold standard procedure for joint preservation in symptomatic developmental dysplasia of the hip (DDH). Hip arthroscopy (HA) and open arthrotomy have been used to correct intra-articular pathology at the time of PAO, but there is limited data regarding differences in outcomes between these techniques when performed at the time of PAO. The aim of this study was to determine if short-term clinical outcomes differed between patients managed with HA versus arthrotomy to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…In addition, the HOOS has been found to be the most appropriate patient-reported outcome measure in patients undergoing PAO compared to the Western Ontario and Osteoarthritis Outcome Score (WOMAC) and the modified Harris Hip Score (25). The improvements found in all five subscales of HOOS in our study are similar to previously reported data on patients with hip dysplasia in other databases with prospective data collection (25,32,33), although previous studies compared patient-reported outcomes preoperatively to 12 months postoperatively. Another strength is the use of the same two blinded raters performing all radiographic measurements and investigating their inter-rater reliability.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the HOOS has been found to be the most appropriate patient-reported outcome measure in patients undergoing PAO compared to the Western Ontario and Osteoarthritis Outcome Score (WOMAC) and the modified Harris Hip Score (25). The improvements found in all five subscales of HOOS in our study are similar to previously reported data on patients with hip dysplasia in other databases with prospective data collection (25,32,33), although previous studies compared patient-reported outcomes preoperatively to 12 months postoperatively. Another strength is the use of the same two blinded raters performing all radiographic measurements and investigating their inter-rater reliability.…”
Section: Discussionsupporting
confidence: 90%
“…With regard to the technique used to visualize the joint, the findings of the present cohort demonstrate parity between arthrotomy and arthroscopic techniques in joint examination. This has previously been reported for patients undergoing PAO for classic hip dysplasia [ 28 ]. Arthroscopy is increasingly done today at the time of PAO to examine and treat the labrum and to perform a femoral head–neck junction osteochondroplasty, although some surgeons still perform an arthrotomy after acetabular correction to assess impingement and perform the osteochondroplasty.…”
Section: Discussionsupporting
confidence: 70%
“…Supporting the treatment of labral pathology at the time of surgery, the presence of labral lesions [ 29 ] or a detached labrum [ 30 ] has been associated with inferior outcomes or a risk of repeat hip arthroscopy, respectively, after PAO, suggesting that intraarticular procedures may positively influence labral health in excess of the mechanical offloading achieved through PAO alone. However, previous reports of 1 year PROM in patients receiving PAO with intraarticular procedures did not detect a differential effect of major versus minor interventions [ 28 ]. Longer follow-ups of 4.5 years in patients receiving PAO report that postoperative pain is not influenced by labral repair, excision or no treatment [ 8 ].…”
Section: Discussionmentioning
confidence: 90%
“…Third, this study did not account for other factors that may influence PROM or natural history following PAO, namely the accuracy and degree of acetabular correction. Recent data have shown that patients with more severe baseline DDH experience greater improvements in PROM [ 25 ], and the natural history of the native hip is improved with the restoration of ‘normal’ radiographic parameters of the acetabular fragment [ 26 ].…”
Section: Discussionmentioning
confidence: 99%